2020
DOI: 10.3389/fimmu.2020.01745
|View full text |Cite
|
Sign up to set email alerts
|

When the Damage Is Done: Injury and Repair in Thymus Function

Abstract: Even though the thymus is exquisitely sensitive to acute insults like infection, shock, or common cancer therapies such as cytoreductive chemo-or radiation-therapy, it also has a remarkable capacity for repair. This phenomenon of endogenous thymic regeneration has been known for longer even than its primary function to generate T cells, however, the underlying mechanisms controlling the process have been largely unstudied. Although there is likely continual thymic involution and regeneration in response to str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 190 publications
(219 reference statements)
1
48
0
Order By: Relevance
“…Based on the success of long-sought observations in histology and embryology, recent progress in and applications of single-cell transcriptome technologies have unveiled the functional diversity of such non-TEC stromal cells and highlighted their immunological functions. Along with pioneering studies on the regeneration of TECs ( 128 131 ), a better understanding of the cellular and molecular basis of the entire set of thymic stromal cells will provide valuable insights toward the in vivo reconstitution of the thymus for future therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the success of long-sought observations in histology and embryology, recent progress in and applications of single-cell transcriptome technologies have unveiled the functional diversity of such non-TEC stromal cells and highlighted their immunological functions. Along with pioneering studies on the regeneration of TECs ( 128 131 ), a better understanding of the cellular and molecular basis of the entire set of thymic stromal cells will provide valuable insights toward the in vivo reconstitution of the thymus for future therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the everyday insults like stress and infection, the thymus is also exquisitely sensitive to cytoreductive therapies like chemotherapy and radiation, often used in the conditioning required for successful hematopoietic cell transplant (HCT) [ 13 , 14 ]. In mouse models, studies have found that after both total body irradiation (TBI) or chemotherapy, in addition to the direct depletion of highly proliferative thymocytes, there is significant damage to the nonhematopoietic epithelial microenvironment resulting in reduced T cell development [ 15 , 16 ]; which may result from the relatively high rate of turnover of some TEC subsets [ 17 ]. Although damage and recovery are worse in older individuals whose thymus has already undergone significant involution, prolonged T cell depletion after cytoreductive therapies can be dangerous in even relatively young individuals; which has been shown in cohorts of human patients [ 18 ] and in mice [ 19 , 20 ].…”
Section: Acute Damage: Restoring T Cell Numbersmentioning
confidence: 99%
“…One approach used to identify therapeutic strategies to boost thymic function has been to exploit the mechanisms that govern endogenous regeneration from acute injury [ 16 ]. As described above, studies have found that IL-22, KGF, RANKL, and BMP4 are all involved in the endogenous response to injury, and all can be utilized to boost thymic function in the setting of acute damage [ 77 , 88 , 95 , 96 ].…”
Section: Repairing the Thymus In Settings Of Acute And Chronic Injurymentioning
confidence: 99%
“…The thymus is extremely sensitive to damage and exposure to acute or chronic insults results in a pronounced decline in cellularity, a phenomenon known as thymic atrophy ( 41 , 42 ). For example, we recently demonstrated thymic atrophy displayed by mice under microgravity (0 g) conditions during spaceflight, which was partially mitigated by exposure to 1 g during spaceflight ( 43 ).…”
Section: Adult Tec Progenitors During Recovery From Stress-induced Damentioning
confidence: 99%
“…For example, we recently demonstrated thymic atrophy displayed by mice under microgravity (0 g) conditions during spaceflight, which was partially mitigated by exposure to 1 g during spaceflight ( 43 ). After resolution of acute insults such as infections, cytoreductive therapies, and emotional and physical discomfort, the thymus is able to regenerate, although its capacity declines with age ( 41 , 42 ). To study this endogenous thymic regeneration, researchers have employed viral and bacterial infections, sub-lethal irradiation, and synthetic corticosteroid injections to model acute insults ( 44 50 ).…”
Section: Adult Tec Progenitors During Recovery From Stress-induced Damentioning
confidence: 99%